The (racial) implications of “special favors” - Nicholas T Davis (Research & Politics, 2023)
In this short manuscript, I explore the predictive validity of a common component of racial resentment—(dis)agreement with the idea that minority racial groups need special favors to get ahead. Specifically, this analysis takes advantage of different “special favors” questions included in the Cooperative Congressional Election Studies (CCES) 2012-2014 Panel Study to assess whether affirmative action preferences are uniquely racialized. I find that (1) respondents react differently to the special favors instrument on the basis of the racial group in question, (2) these assessments vary among liberals and conservatives, and (3) they predict racialized outcomes stereotypically associated with a given racial group. These findings dovetail with recent work that illustrates an ideological sorting of such measures, while offering modest evidence that a prominent instrument used in symbolic racism scales is, in fact, race-coded to specific target groups.